Visual Perception in Social Networks of Real and AI-Synthesized Photographs - Yucra-Mamani, Yudi Janeh; Torres-Cruz, Fred; Aragón Cruz, Walker Ernesto (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This descriptive and cross-sectional study examines visual perception of real and AI-generated photographs on Facebook, focusing on the highland context of Puno, Peru. Through a survey administered via Google Forms, data were collected from 215 participants, and images were evaluated using a technical sheet by 24 experts from January to February 2024. The findings indicate positive public reactions, a preference for authentic images, and an ability to identify distortions in those generated by AI. Experts highlighted favorable technical aspects of the synthesized images. These results suggest a complex interplay between photographic authenticity and AI technology in visual perception.